A preliminary study of real-time capturing and sharing of routine health data among the public health professionals. - Ganiga, Raghavendra; Pai, Radhika; Manohara Pai, M; Sinha, Rajesh (Indian Journal of Community Medicine)
Context: Electronic health record (EHR) has the potential to make available the real-time data of the patient to the healthcare professionals by connecting all levels of the public health system, irrespective of their geographical boundaries. Aim: This study aims to test the capturing and sharing of real-time patient data at primary, secondary, and the tertiary level. Settings and Design: The cloud-based EHR system developed earlier was used to capture real-time data of the patient visiting a primay health center (PHC) in Udupi District of Karnataka. Subjects and Methods: About 100 patient records including laboratory and pharmacy data have been captured into the EHR system. The confidentiality of patient data is assured. Results: The result of the study indicated no errors while capturing and sharing the patient data in real time. The system also evidenced the availability of vital statistics about the patient visiting PHCs. The system also allowed the professionals at referral level to view patient data for providing quality healthcare. Conclusion: EHR plays a vital role in capturing, storing, and sharing patient data for providing quality healthcare and it should be made mandatory by the central health agencies in the provision of patient care and reporting of notifiable communicable diseases at all levels.